SURVEY TINGKAT KEBUGARAN JASMANI PADA ALTET PENCAK SILAT KOTA DOBO - Gainau, Yomima Getreda; Tahapary, Johni M; Pieter, Marsiline (JARGARIA SPRINT: Journal Science of Sport and Health, 2023)
This study aims to determine the level of physical fitness of th This research belongs to the type of survey research. The population of this research is the pencak silat athletes in the city of Dobo with a total sample of 16 athletes consisting of 6 women and 10 sons. The data analysis technique used in this research is descriptive quantitative. The data collected from each test item is rough data from the results of each test item which is converted into a value by conserving the coarse data results of each test item using the Indonesian Physical Fitness Test (TKJI) assessment table for children aged 16-19 years. from the physical quality development center 2010. Based on the results of data analysis, this study concludes that: the level of physical fitness of the pencak silat athletes in the city of Dobo with very good category 6,25% (1 athlete), good 31,25% (5 athletes), moderate as much as 62,5% (10 athletes), less 0 % ( 0 athletes), very less 0% (0 athletes). have a good level of physical fitness.